OS 06-07 COMBINING SHORT- AND LONG-TERM RISK SCORES IN PRIMARY PREVENTION OF MAJOR CARDIOVASCULAR DISEASE EVENTS IN LOW INCIDENCE POPULATIONS: AN ASSESSMENT OF CLINICAL UTILITY. (September 2016) - Veronesi, Giovanni; Giampaoli, Simona; Gianfagna, Francesco; Palmieri, Luigi; Vanuzzo, Diego; Grassi, Guido; Cesana, Giancarlo; Ferrario, Marco M.
Abstract : Objective: To evaluate the clinical utility of the CAMUNI-MATISS 20-year risk score, recently validated for the Italian population, as additional screening tool for individuals at "low" (ESC-SCORE Project predicted 10-year risk ⩽ 1%; no preventive action), "intermediate" (ESC-SCORE 1–4%; lifestyle modification/statin treatment) and "high" risk (ESC-SCORE≥ 4% or diabetes; statin treatment) according to the Italian regulation. Design and method: 40–65 years old initially CVD-free participants to 7 population-based cohorts enrolled in Northern and Central Italy between 1986 and 1996 were followed-up (median 16 years, IQR: 12–20) to the first occurrence of coronary event or ischemic stroke (fatal or non-fatal), coronary or carotid revascularizations. The CAMUNI-MATISS 20-year score includes age, total- and HDL-cholesterol, systolic blood pressure, anti-hypertensive treatment, smoking and diabetes. We estimated the Net Benefit (NB), a weigthed difference between true and false positives. To assess the utility of the CAMUNI-MATISS score, weights were set such that the NB of using the ESC-SCORE risk alone was zero. Results: Study sample included 3935 men (468 events, observed 20-year risk: 15%) and 4393 women (210 events, 20-year risk: 7%). The "intermediate" risk category accounted for 76% of men, 40% of which could have been selected for preventive action based on their predicted 20-year risk, with a Net Benefit of 4.1 (95% CI: 2.7–5.6). In the "high" risk category (21% of men), the NB of the 20-year risk score to trigger treatment intensification was 7.1 (1.8–10.9). The "low" and "intermediate" risk categories accounted for 74% and 21% of women, respectively. About 40% in each category could have been selected for preventive action based on their predicted 20-year risk, with a Net Benefit of 1.3 (95%CI:0.6–2.1) and 4.1 (2.7–5.6), respectively. Conclusions: In the Italian population, a combination of validated short- and long-term CVD risk scores allows selecting for preventive action initiation/intensification individuals whose risk is currently not fully addressed, and reducing un-necessary, costly overtreatment.